Heavy Metal Estimation and Quality Assurance Parameters for Water Resources in the Northern Region of Pakistan - Hayder, Rizwan; Hafeez, Muhammad; Ahmad, Pervaiz; Memon, Najma; Khandaker, Mayeen Uddin *; Elqahtani, Zainab Mufarreh; Al-Buriahi, M. S.; Mahmoud, Zakaria M. M.; Ahmed, Muhammad Naeem (MDPI, 2022)
The current study investigates the water quality parameters of drinking water resources in District Neelam (DNLM), Azad Jammu & Kashmir (AJK), Northwestern Pakistan. The studied area has been recently reported with many waterborne diseases, which probed this analytical study. The samples were aseptically collected from springs, taps, and surface water bodies. The water quality parameters, such as physical, microbiological, anions, and heavy metals, were tested. Results showed that the electrical conductance (EC) and total dissolved solids (TDS), were 974.60 µS/cm and 912.10 mg/L, respectively, exacerbating the quality of drinking water in DNLM. For microbial water testing, we used 3M-Petrifilms as a detection source, which could separate coliform bacteria from E. coli by creating unique surface chromophores. Out of sixty collected samples, 76% had bacterial contamination. Nitrite, nitrate, and phosphate (9.8, 15.0, and 15.1 mg/L), were also surpassing the safe limits of the World Health Organization (WHO) standards for water quality measurement. The heavy metals, i.e., As, Cr, Cu, and Pb were also tested in current analysis. Pb and Cr (0.04 mg/L and 0.06 mg/L) exceeded from safe drinking water guidelines of the WHO and more than 50% of the collected samples had Pb as a major water pollutant in DNLM. Poor waste management, open sludge discharge, lack of municipality measures, and mineral leaching into the freshwaters of DNLM due to mining and metal extraction processes were the main sources of water pollution in the region. The inorganic pollutants were responsible for the sudden rise of different malignancies and other fatal diseases (vital organ failures and reproductive disorders) in the region, which has not been reported in the past. The current investigation yielded useful baseline data of the drinking water reserves of NW Pakistan that could help to develop techniques for the mitigation of water pollutants present in the region.